Rethinking Indonesia’s Interests in the BRI Projects under Jokowi’s Presidency: The Pros and Cons - Theresia Octastefani; Mohammad Romadhoni (Journal of Governance, 2023)
Under Jokowi’s presidency, the BRI project was able to further strengthen the bilateral ties between Indonesia and China. This study aims to analyse and focus on: first, the pros and cons of Indonesia's interests in the BRI projects under Jokowi's presidency; second, the political leadership of Jokowi in managing and implementing BRI projects in Indonesia. This study used a qualitative approach to gather comprehensive data through a literature review. As an analytical tool for this research, the author used the political leadership theory by Kalevi Jaakko Holsti. The finding showed that, first, those who are pro-BRI will provide full support, supervision, and evaluation from year to year. Meanwhile, there are several cons to the BRI project due to fear of the debt trap, the influx of Chinese workers, the environmental damage, the overlapping maritime claims, anti-communist sentiment, and the image of Chinese products. The negative sentiment towards the BRI project can be eased with a soft-infrastructure approach that touches community (people-to-people) bonds. Second, regarding Jokowi's eight-year leadership, Jokowi's type of political leadership is more directed as a conciliator, especially in the China BRI project. It is based on Jokowi's record of making China a good partner and big brother.